A survey into the use of priming techniques implemented by athletes and coaches to improve athletic performance - Collins, J.; Bishop, C.; Hills, F.; Spiegelhalter, A.; Cohen, R.; Turner, A. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to examine the frequency and modes of psychological priming techniques and strategies being implemented by athletes of a variety of performance levels. A 15-question, anonymous questionnaire was developed and shared via social media sites. The survey implemented a quantitative method approach to collect background information (e.g., demographics, competition, and training history), the prevalence of priming, and the methods used. Ninety subjects met the inclusion criteria (71 men, 18 women, and 1 subject did not identify their sex), with a median age of 28 ± 7.47 years (range, 24-33 years) and training experience of 11 ± 7.57 years (range, 8-18 years). Self-selected participation level accounted for 11 professional, 17 semiprofessional, and 54 amateur-level athletes. Priming strategies were implemented by 79% of subjects without the use of a coach, 10% used strategies with their coach, and 11% did not prime. For athletes, music was the preferred choice (27%), followed by instructional self-talk (24%), motivational self-talk (23%), applied physical actions (20%), and watching videos clips (6.3%). Coaches preferred motivational statements with 55% implementing this technique, followed by 27% using inspiring team talks, and only 18% playing music. Of those who implemented a priming strategy, 66% found them to be either "very" or "extremely" effective," With 38% of subjects feeling that priming accomplished this through increased motivation, 22% felt that it reduced their fear and anxiety, 21% thought that it improved their intensity, 15% felt that it increased strength and power, and 2% felt that it improved endurance. The chi-square test also found a significant (fc = 0.27; p = 0.011) relationship with the use of priming to increase motivation. These results demonstrate that priming strategies are being used irrespective of coach intervention; therefore, educating coaches and athletes on the implementation of priming techniques has its place when aiming to improve athlete performance.